The idea of Self in young adults with psychological difficulties and uncertainty in the phase of the psychosocial transition to the university context: a study with Self Characterization Analysis technique in a Counselling workshop - Mollo, Monica; Savarese, Giulia; Carpinelli, Luna; Pecoraro, Nadia; D'Elia, Daniela (Psychology Hub, 2025)
The entry of students into the world of the university coincides with what in the literature is called "psycho-social transitions", described not rarely, in the psychological field, as stressful and uncertainty, events, to the point of making the person more psychologically vulnerable. In order to evaluate the transition process, we used the mixed quantitative-qualitative method in pre/post-intervention modalities of the counseling workshop in which n° 6 students (mean age=22.83, SD=1.47) who requested psychological support from the University Counselling Centre participated. The Symptom Check-List-90-R and the Rosenberg Self-Esteem Scale were used to assess the psychopathological framework, while Self-characterisation was used to investigate the constructs of the Self. The psychopathology indexes present a general altered state in PRE-phase: GSI=59.67±11.37, PSDI=62±9.25, PST=54.67±12.97. On the other hand, in the post-intervention phase of the counseling laboratory, it is possible to note a scaling down of this alteration, and, in fact, the scores of the clinical scales are within the normative range. Furthermore, as far as self-esteem is concerned, it can be verified that the average score in the PRE-phase is 13 (SD=1.73) recording low self-esteem, while in the POST-phase a strengthening of the dimension under analysis is recorded as the average score is 21 (SD=2.82). Empowering one's interpersonal resources means being able to adopt a new perspective by nurturing a greater sense of self-efficacy, from 'I am as I think others see me' to 'I am in relation to my feelings, others, my history, my projects', which highlights a different way of constructing the 'Self-Image'.